2006
DOI: 10.1038/modpathol.3800578
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin expression and localization in various types of carcinomas of the thyroid gland

Abstract: Fibrillin is an extracellular matrix (ECM) glycoprotein, a main component of microfibrills, suggested to support cell attachment and to impact cell differentiation and migration. The aim of this study was to investigate fibrillin-1 expression in thyroid carcinomas at mRNA and protein level, since ECM proteins are suggested to be of great importance for the metastatic potential of carcinomas. RNA was extracted from 13 thyroid carcinoma cell lines and RT-PCR analysis with gene-specific primers revealed fibrillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…All these genes were chosen based on their functional involvement in breast cancer. Up regulated genes included s elenoprotein plasma protein (SEPP1) and decorin (DCN) which have an antimetastatic role in breast cancer (22-24) fibrillin1 (FBN1), aldehyde oxidase 1 (AOX1) and prostagladin E receptor 2 (PTERG2) which are known to promote tumor growth (25-27) and, surprisingly, angiopotein1 (ANGPT1 ) which when over expressed has antitumor properties (28). …”
Section: Resultsmentioning
confidence: 99%
“…All these genes were chosen based on their functional involvement in breast cancer. Up regulated genes included s elenoprotein plasma protein (SEPP1) and decorin (DCN) which have an antimetastatic role in breast cancer (22-24) fibrillin1 (FBN1), aldehyde oxidase 1 (AOX1) and prostagladin E receptor 2 (PTERG2) which are known to promote tumor growth (25-27) and, surprisingly, angiopotein1 (ANGPT1 ) which when over expressed has antitumor properties (28). …”
Section: Resultsmentioning
confidence: 99%
“…Although the mutation of FBN1 is a main pathogenesis of Marfan syndrome and Weill-Marchesani syndrome [41, 42], the overexpression of FBN1 is also detected in cancer tissues [43]. Several studies have shown that FBN1 is associated with TGF-beta signaling [44, 45], while the TGF-beta signaling is reportedly to induce EMT that may in turn regulate the expressions of E-cadherin, beta-catenin, and MMPs [4649].…”
Section: Discussionmentioning
confidence: 99%
“…FBN2 (fibrillin 2), which is homologous to FBN1, is highly expressed in embryonic tissues [Samuel et al, 2003]. Recently, FBN1 has been shown to play a key role in lung development [Chen et al, 2005] and has been implicated in cell attachment, differentiation, and migration [Tseleni-Balafouta et al, 2006]. The well-known hSSC marker c-kit is essential for the maintenance of PGCs in both sexes.…”
Section: Discussionmentioning
confidence: 98%